2018
DOI: 10.3389/fpsyg.2018.00277
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Functional Near-Infrared Spectroscopy (fNIRS) in Studying Cognitive Development: The Case of Mathematics and Language

Abstract: In this review, we aim to highlight the application of functional near-infrared spectroscopy (fNIRS) as a useful neuroimaging technique for the investigation of cognitive development. We focus on brain activation changes during the development of mathematics and language skills in schoolchildren. We discuss how technical limitations of common neuroimaging techniques such as functional magnetic resonance imaging (fMRI) have resulted in our limited understanding of neural changes during development, while fNIRS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 95 publications
1
59
0
1
Order By: Relevance
“…Many optical techniques were designed to utilize multiple forward scattered light, many of which date back long before the invention of OCT. For example, functional near‐infrared spectroscopy (fNIRS) was first demonstrated in the late 1970s, in which separate illumination and detection pathways were used to measure cortical oxygenation during hyperventilation . Since then, much of the fNIRS literature reported that the photon trajectories between source‐detector pairs exhibit banana‐shaped profiles (ie, deep probing photons have higher probability of traveling further away from illumination along the lateral direction) .…”
Section: Introductionmentioning
confidence: 99%
“…Many optical techniques were designed to utilize multiple forward scattered light, many of which date back long before the invention of OCT. For example, functional near‐infrared spectroscopy (fNIRS) was first demonstrated in the late 1970s, in which separate illumination and detection pathways were used to measure cortical oxygenation during hyperventilation . Since then, much of the fNIRS literature reported that the photon trajectories between source‐detector pairs exhibit banana‐shaped profiles (ie, deep probing photons have higher probability of traveling further away from illumination along the lateral direction) .…”
Section: Introductionmentioning
confidence: 99%
“…This finding shows that in an ecologically valid setting, namely dealing with numbers and letters in a written production as in the academic setting, the neural correlates of simply copying numbers and letters might not differ. Interestingly, the similarity of the findings in the two different samples of children reveals the reliability of fNIRS as an appropriate neuroimaging method in children and in the context of education neuroscience (Soltanlou, Sitnikova, et al, 2018). Further research needs to investigate whether number and letter copying have the same neural correlates at younger and older ages.…”
Section: Discussionmentioning
confidence: 85%
“…The prefrontal cortex (PFC) is known to be involved in processes of high order cognition such as counting or calculating while the temporo-parietal junction (TPJ) is involved in social functions such as empathy and mentalizing (Fuster, 2000 ; Van Overwalle, 2009 ; Carter et al, 2012 ; Artemenko et al, 2018a , b ; Soltanlou et al, 2018a , b ). Thus, we hypothesized that activity in the teacher's TPJ would couple with that of the child's PFC.…”
Section: Case Studiesmentioning
confidence: 99%